Inclusion in school: physical education teachers’ perceptions of students with impairments - Tomasz Michał Korczyński; Piotr Marek (Journal of Modern Science)
Objectives Using data from sociological research conducted among teachers of Polish schools in 2023, the authors investigated the attitudes of teachers towards students with impairments (SWI) participating in the program School Sports Club (SKS).